2019
DOI: 10.7554/elife.43717
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized reactivation maintains and reinforces memories despite synaptic turnover

Abstract: Long-term memories are believed to be stored in the synapses of cortical neuronal networks. However, recent experiments report continuous creation and removal of cortical synapses, which raises the question how memories can survive on such a variable substrate. Here, we study the formation and retention of associative memory in a computational model based on Hebbian cell assemblies in the presence of both synaptic and structural plasticity. During rest periods, such as may occur during sleep, the assemblies re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 91 publications
3
76
1
Order By: Relevance
“…In the case discussed in Section 2.2, in contrast, the memories formed are "silent" (elsewhere classified as "transient" [38]), very different from the persistent activity usually considered in working memory tasks (elsewhere classified as "persistent", or "dynamic" [38]). The latter type of activity seems to be consistent with Hebbian plasticity models [10,30,46], and one may wonder what is the relation of our model with these alternative models.…”
Section: Memory Engrams Emerge Because the Homeostatic Rule Acts As supporting
confidence: 66%
See 2 more Smart Citations
“…In the case discussed in Section 2.2, in contrast, the memories formed are "silent" (elsewhere classified as "transient" [38]), very different from the persistent activity usually considered in working memory tasks (elsewhere classified as "persistent", or "dynamic" [38]). The latter type of activity seems to be consistent with Hebbian plasticity models [10,30,46], and one may wonder what is the relation of our model with these alternative models.…”
Section: Memory Engrams Emerge Because the Homeostatic Rule Acts As supporting
confidence: 66%
“…Recently, [10] showed that Hebbian structural plasticity could be the force behind memory consolidation through a process of stabilization of connectivity, which is based on the existence of an attractive fixed point in the plastic network structure. In our model, because of the decay of the slow manifold, memories are never permanent, and repeated stimulation is necessary to stabilize them.…”
Section: Memory Engrams Emerge Because the Homeostatic Rule Acts As mentioning
confidence: 99%
See 1 more Smart Citation
“…In living animals long-term recordings observed both complete [23] and, more often, incomplete structural remodeling [24]. We will nd drifting assemblies also in absence of remodeling, suggesting that they occur in intermediate cases as well, for example when turnover is less random through weight dependence or incomplete [3,24,25].…”
Section: Spontaneous Remodeling Gives Rise To Drifting Assembliesmentioning
confidence: 77%
“…Another hypothesis is that any memory degradation due to fluctuations is counteracted by restorative, systematic plasticity processes that allow circuits to continually 'relearn' stored associations. The source of information for the systematic plasticity term could come from an external reinforcement signal Kappel et al (2018), from interactions with other circuits Acker et al (2018), or spontaneous, network-level reactivation events Fauth and van Rossum (2019). A final possibility is that we rarely observe behavioural states in which an animal is not learning, and that unobserved behavioural changes account for apparent fluctuations in brain connectivity in any given experiment.…”
Section: Discussionmentioning
confidence: 99%